Transmission resin composition, adhesive, optical film and display device

By using a transparent resin composition of natural fibers with an average particle size of 2 μm to 100 μm in a liquid crystal display device, polarization is eliminated and image color changes of the display screen is suppressed, and the problem of reducing visual recognition in the prior art is solved, thereby achieving higher visual effects and lower costs.

CN119546989APending Publication Date: 2025-02-28SAIDEN CHEM IND +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380053883.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-05-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art cannot effectively suppress the color change of users wearing polarized sunglasses when observing the display screen in the liquid crystal display device, resulting in a decrease in visual recognition.

Method used

A transparent resin composition is used, which contains natural fibers having an average particle size of 2 μm to 100 μm, for eliminating polarization and thereby suppressing image color changes in the display screen.

Benefits of technology

It is realized that the image color change of the display screen is suppressed when the user observes the display screen, which improves visual recognition and reduces the cost of the display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546989A_ABST
    Figure CN119546989A_ABST
Patent Text Reader

Abstract

The light-transmitting resin composition comprises a transparent resin and a natural fiber having an average particle diameter of 2-100 [mu] m, and is used to eliminate polarization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a light-transmitting resin composition, an adhesive, an optical film and a display device. Background Art

[0002] The liquid crystal display device comprises: a liquid crystal layer; and two polarizing plates, which are arranged to sandwich the liquid crystal layer and have mutually orthogonal transmission polarization directions. Therefore, the light emitted from the display screen of the liquid crystal display device becomes linearly polarized light. It should be noted that if it is a device that emits light in a polarized state, it is not limited to the liquid crystal display device. For example, when a user wearing polarized sunglasses observes the display screen, the brightness of the display screen visually recognized by the user is lower than when the display screen is observed without wearing polarized sunglasses. This is because, according to the angle formed by the polarization direction of the emitted light from the display screen and the transmission polarization direction of the polarized sunglasses, the emitted light from the display screen will not pass through the polarized sunglasses. For example, when the polarization direction of the emitted light is orthogonal to the transmission polarization direction of the polarized sunglasses, the user wearing the polarized sunglasses cannot visually recognize the display screen at all. Such a phenomenon is called blackout. Therefore, in order to solve the problem of reduced visual recognition when a user wearing polarized sunglasses observes a display screen, the following technology is proposed.

[0003] Patent Document 1 discloses a technology in which a phase difference plate (quarter wavelength plate) is provided on the user side of a polarizing plate on the user's visual recognition side in a liquid crystal display device to convert linear polarization from a display screen into circular polarization.

[0004] Patent document 2 discloses the following technology: in a liquid crystal display device, a polymer film with very high birefringence (i.e., very large delay amount) is arranged on the user side compared to the polarizing plate on the user's visual recognition side, thereby shortening the transmittance variation period corresponding to the wavelength generated between the polarizing plate and the polymer film.

[0005] Patent document 3 discloses the following technology: a medium transparent to visible light; and a plurality of crystalline materials dispersed in the medium having birefringence, thereby randomizing the polarization state of incident visible light and emitting visible light with a lower polarization degree than the visible light incident on the transparent medium.

[0006] Patent Document 4 discloses a technique for eliminating linear polarization by using a film in which extremely short fibers are dispersed in a light-transmitting resin.

[0007] Patent Document 5 discloses a technique of eliminating linear polarization by making a transparent matrix material contain extremely short fibers.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2005-352068

[0011] Patent Document 2: Japanese Patent Application Publication No. 2011-107198

[0012] Patent Document 3: International Publication No. 2019 / 026854

[0013] Patent Document 4: Japanese Patent Application Publication No. 2009-217192

[0014] Patent Document 5: Japanese Patent Application Publication No. 2008-310310 Summary of the invention

[0015] Problems to be solved by the invention

[0016] However, in the technology of patent document 1, the wavelength dependence (dispersion characteristics) of the phase difference in the phase difference plate is not taken into account, so the user will recognize the color mottle of the display screen. In the technology of patent document 2, when a light source composed of a combination of red, green and blue light-emitting diodes (RGB-LED) with relatively narrow spectral widths of each luminous spectrum is used as the light source of the liquid crystal display device, the user will recognize the color mottle of the display screen. In the technology of patent document 3, the clarity and contrast ratio of the display screen are insufficient. In the technology of patent document 4, the haze of the film is large, so the chromaticity change, clarity and contrast are not good. In the technology of patent document 5, the chromaticity change, clarity and contrast ratio when the user visually recognizes the display screen are insufficient. In this way, in the technologies of patent documents 1 to patent document 5, there is the following problem: when the user observes the display screen, the color of the image of the display screen is displayed in a color different from the original color.

[0017] Therefore, an object of the present invention is to provide a light-transmitting resin composition, an adhesive, an optical film, and a display device that suppress a change in the color of an image on a display screen when a user observes the display screen.

[0018] Solutions for solving problems

[0019] In order to achieve the object of the present invention, a light-transmitting resin composition according to one embodiment of the present invention has the following configuration: That is, the light-transmitting resin composition comprises a transparent resin and natural fibers having an average particle size of 2 μm to 100 μm, and is used for depolarization.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide a light-transmitting resin composition, an adhesive, an optical film, and a display device that suppress a change in the color of an image on a display screen when a user observes the display screen.

[0022] Other features and advantages of the present invention will become apparent from the following description with reference to the accompanying drawings. In the accompanying drawings, the same or similar components are denoted by the same reference numerals. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are included in the specification and constitute a part of the specification. The accompanying drawings illustrate embodiments of the present invention and together with the description of the embodiments, explain the principles of the present invention.

[0024] Figure 1A The figure shows a polarization microscope photograph of an acrylic pressure-sensitive adhesive containing silk powder.

[0025] Figure 1B Yes Figure 1A A magnified image of a portion of the overall image.

[0026] Figure 1C This is a diagram showing an SEM image of an example of silk powder.

[0027] Figure 2A The figure shows the SEM image of the silk powder SP.

[0028] Figure 2B The figure shows a SEM image of silk powder S15.

[0029] Figure 2C The figure shows a SEM image of silk powder Nervis natulus.

[0030] Figure 3 It is an exploded perspective view showing an example of the display device according to the present embodiment.

[0031] Figure 4 A is a diagram showing an image obtained by photographing a display screen to which the optical film of Example 3 is attached in a crossed Nicol state.

[0032] Figure 4 B is a diagram showing an image obtained by photographing a display screen to which the optical film of Comparative Example 1 is attached in a crossed Nicol state.

[0033] Figure 5 This is a schematic diagram for explaining the method of evaluating rainbow mottle.

[0034] Figure 6 This is a schematic diagram for explaining a method for evaluating the wavelength dependency of transmittance.

[0035] Fig. 7A This is a diagram showing the colorimetric measurement results of a reference example of measurement condition 1.

[0036] Figure 7BThis is a diagram showing the colorimetric measurement results of Example 3 (measurement method 1) under measurement condition 1.

[0037] Figure 7C This is a diagram showing the colorimetric measurement results of Example 3 (measurement method 2) under measurement condition 1.

[0038] Fig.7D This is a diagram showing the colorimetric measurement results of Example 5 (measurement method 1) under measurement condition 1.

[0039] Fig. 7E This is a diagram showing the colorimetric measurement results of Example 5 (measurement method 2) under measurement condition 1.

[0040] Figure 7F This is a diagram showing the chromaticity measurement results of Example 6 (measurement method 1) under measurement condition 1.

[0041] Figure 7G This is a diagram showing the chromaticity measurement results of Example 6 (measurement method 2) under measurement condition 1.

[0042] Figure 7H It is a graph showing the chromaticity measurement results of Comparative Example 7 under measurement condition 1.

[0043] Fig. 8A This is a diagram showing the colorimetric measurement results of a reference example under measurement condition 2.

[0044] Figure 8B This is a diagram showing the chromaticity measurement results of Example 3 (measurement method 1) under measurement condition 2.

[0045] Figure 8C This is a diagram showing the chromaticity measurement results of Example 3 (measurement method 2) under measurement condition 2.

[0046] Fig.8D This is a diagram showing the chromaticity measurement results of Example 5 (measurement method 1) under measurement condition 2.

[0047] Fig. 8E This is a diagram showing the chromaticity measurement results of Example 5 (measurement method 2) under measurement condition 2.

[0048] Figure 8F This is a diagram showing the chromaticity measurement results of Example 6 (measurement method 1) under measurement condition 2.

[0049] Figure 8G This is a diagram showing the chromaticity measurement results of Example 6 (measurement method 2) under measurement condition 2.

[0050] Figure 8H This is a diagram showing the chromaticity measurement results of Comparative Example 7 under measurement condition 2.

[0051] Fig.9A This is a graph showing the wavelength dependence of transmittance in the parallel Nicol state.

[0052] Fig. 9B Graph showing the wavelength dependence of transmittance in the orthogonal Nicol state. DETAILED DESCRIPTION

[0053] Hereinafter, the embodiments are described in detail with reference to the accompanying drawings. It should be noted that the following embodiments are not intended to limit the invention involved in the claims, and not all combinations of the features described in the embodiments are necessary for the present invention. Two or more of the multiple features described in the embodiments may be combined arbitrarily. In addition, the same or identical configurations are marked with the same figure mark, and repeated descriptions are omitted.

[0054] <Light-transmitting resin composition>

[0055] A light-transmitting resin composition according to one embodiment of the present invention includes a transparent resin and natural fibers having an average particle size of 2 μm to 100 μm, and is used for depolarization.

[0056] A light-transmitting resin composition according to one embodiment of the present invention comprises: a transparent resin; and natural fibers having a maximum retardation of 300 nm to 1300 nm and an average particle size of 2 μm to 100 μm, wherein the natural fibers are contained in an amount of 1 to 20 parts by mass relative to 100 parts by mass of the transparent resin for eliminating polarization.

[0057] Here, the mechanism is described in which the light-transmitting resin composition contains natural fibers having the above-specified average particle size and / or maximum retardation, thereby producing an effect of suppressing color change of an image on a display screen formed by adhering an optical film or the like described later.

[0058] Figure 1A This is a polarization microscope photograph of an acrylic adhesive containing silk powder. Silk powder refers to silk powder used by the inventors in the previous research related to the present invention, and is silk powder having an average particle size (about 20 μm) equivalent to that of silk powder SP described later. It should be noted that the acrylic adhesive refers to the acrylic adhesive of Example 9 described later.

[0059] Figure 1B Yes Figure 1A A magnified image of a portion of the overall image. Figure 1C This is a diagram showing an SEM image of an example of silk powder.

[0060] based on Figure 1BThe interference color shown in FIG. 1 shows that the maximum value of the silk powder retardation R is 600 nm to 700 nm, and the average particle size (thickness) t of the silk powder is about 8 μm. Here, the method for determining the maximum value of the silk powder retardation R is described. The film is set under a polarizing microscope (BX51, Olympus Corporation), and the interference color of the silk powder is observed under the orthogonal Nicol state. The interference color diagram showing the relationship between the retardation R and the interference color is shown in FIG. Figure 1B The interference colors of the silk powder particles are compared to determine the maximum delay R corresponding to the observed interference color. When the maximum delay R is 600nm to 700nm, all interference colors are distributed in the tiny area of ​​the particle. The inventors found that distributing all interference colors in the tiny area of ​​the particle helps to suppress the color change of the image. Here, the birefringence Δn of the silk powder is calculated based on the delay R, the average particle size t and the following formula 1. Therefore, the birefringence Δn is 0.075 to 0.0875.

[0061] Δn=R / t (Formula 1)

[0062] The birefringence Δn (=0.075 to 0.0875) of silk powder is smaller than the birefringence Δn (=0.172) of calcite. As described above, in the present embodiment, the birefringence Δn of silk powder is determined based on the maximum retardation R of silk powder. In addition, the inventors have studied in detail the numerical range of the birefringence Δn of silk powder that can obtain the effect of suppressing the color change of the image based on the birefringence Δn of silk powder calculated in the above and the test results described later. Therefore, from the viewpoint of suppressing the color change of the image, the birefringence Δn of the silk powder involved in one embodiment is 0.013 to 0.15, 0.014 to 0.15, 0.016 to 0.15, 0.018 to 0.15, 0.020 to 0.15 or 0.022 to 0.15. Here, the inventors have found that an acrylic adhesive containing silk powder with a low birefringence Δn has the effect of suppressing the color change of the image of the display screen in the orthogonal Nicol state. Therefore, the inventors have studied how to suppress the color change of an image on a display screen by changing the average particle size of natural fibers contained in a light-transmitting resin composition to various sizes and utilizing the low birefringence Δn of natural fibers.

[0063] Based on the viewpoint of uniformly dispersing natural fibers in a transparent resin to improve permeability, a translucent resin composition according to one embodiment contains less than 20 parts by mass of natural fibers, preferably less than 15 parts by mass of natural fibers, and more preferably less than 10 parts by mass of natural fibers relative to 100 parts by mass of transparent resin. On the other hand, based on the viewpoint of improving polarization elimination performance, a translucent resin composition according to one embodiment contains more than 1 part by mass of natural fibers, preferably more than 1.4 parts by mass of natural fibers, relative to 100 parts by mass of transparent resin. For example, a translucent resin composition according to one embodiment contains 1 to 20 parts by mass of natural fibers, preferably 1.4 to 15 parts by mass of natural fibers, and more preferably 1.4 to 10 parts by mass of natural fibers, relative to 100 parts by mass of transparent resin.

[0064] (Natural Fiber)

[0065] Natural fibers are fibers whose main raw material is a natural raw material. The natural fibers according to one embodiment include at least one of plant fibers and animal fibers.

[0066] From the viewpoint of improving the clarity of the image, the average particle size of the natural fiber involved in one embodiment is 2 μm to 100 μm, preferably 2 μm to 30 μm, and more preferably 3 μm to 25 μm. Here, when the average particle size of the natural fiber is less than 2 μm, the clarity of the image will be reduced. In addition, when the average particle size of the natural fiber exceeds 100 μm, the clarity of the image will be reduced.

[0067] Based on the viewpoint of suppressing the color change of the image, the maximum delay amount of the natural fiber involved in one embodiment is 300nm~1300nm, 300nm~1200nm, 300nm~1100nm or 300nm~1000nm. Here, when the maximum delay amount of the natural fiber is less than 300nm, since all interference colors are not distributed in the micro-region of the particles of the natural fiber, the color of the image will change. In addition, when the maximum delay amount of the natural fiber exceeds 1300nm, although all interference colors are distributed in the micro-region of the particles of the natural fiber, the color of the image will change.

[0068] Based on the viewpoint of suppressing the color change of the image, the birefringence Δn of the natural fiber involved in one embodiment is 0.013-0.15, 0.014-0.15, 0.016-0.15, 0.018-0.15, 0.020-0.15 or 0.022-0.15. Here, when the birefringence Δn of the natural fiber is less than 0.013, the color of the image will change. In addition, when the birefringence Δn of the natural fiber exceeds 0.15, the color of the image will change.

[0069] Figure 2A : is a figure showing a SEM image of silk powder SP. Silk powder SP is a natural fiber contained in the translucent resin composition of the present invention. The average particle size of silk powder SP is about 20 μm. In addition, the average particle size in this specification refers to the particle size (D50; median particle size) with a cumulative value of 50% in the volume-based particle size distribution measured by laser diffraction method. The average particle size can be measured using a particle size distribution measuring device using laser diffraction method.

[0070] Figure 2B : is a figure which shows the SEM image of the silk powder S15. The silk powder S15 is a natural fiber contained in the light-transmitting resin composition of the present invention. The average particle size of the silk powder S15 is about 7 μm to 9 μm.

[0071] Figure 2C This is a diagram showing a SEM image of silk powder Nervis natulus. Silk powder Nervis natulus is a natural fiber contained in the light-transmitting resin composition of the present invention. The average particle size of silk powder Nervis natulus is about 3 μm to 5 μm.

[0072] Plant fibers are fibers extracted from plants, including, for example, cellulose fibers, abaca, hemp, bamboo, coconut fibers, cotton, jute, kapok, flax, ramie, and sisal. It should be noted that the plant fibers may be used alone or in combination of two or more.

[0073] Animal fibers are fibers extracted from animals, including, for example, alpaca, angora, camel, cashmere, mohair (angora goat hair), pashmina, muskox hair, silk, alpaca and wool. Moreover, the animal fibers may be used alone or in combination of two or more.

[0074] In one embodiment, as the natural fiber, a protein natural fiber such as fibroin (for example, silk) or a polysaccharide natural fiber (for example, cellulose) can be used.

[0075] (Transparent resin)

[0076] The transparent resin is a material that becomes the base material of the light-transmitting resin composition and includes inorganic polymers, organic polymers, and hybrid polymers of organic polymers and inorganic polymers.

[0077] The “transparency” of the transparent resin means that the transmittance with respect to light in the visible light region (360 nm to 830 nm) when the film thickness is 50 μm is preferably 80% or more, more preferably 90% or more.

[0078] From the viewpoint of suppressing light scattering of natural fibers, the refractive index of the transparent resin according to one embodiment is 1.4 to 1.7, preferably 1.45 to 1.68.

[0079] Inorganic polymers are polymers that contain inorganic elements and inorganic components, and include natural polymers and synthetic polymers. Natural polymers include glass, silicates, and minerals. Synthetic polymers include polydimethylsiloxane, polycarbosilane, and polyphosphazene.

[0080] Organic polymers include natural polymers and synthetic polymers, wherein the main constituent components of organic compounds such as carbon, hydrogen, oxygen, and nitrogen form a repeating structure. Natural polymers include, for example, cellophane and regenerated cellulose polymers such as triacetyl cellulose. Synthetic polymers include, for example, vinyl resins, polycondensation resins, addition polymerization resins, addition condensation resins, and ring-opening polymerization resins.

[0081] (Vinyl resin)

[0082] Vinyl resins include general-purpose resins such as polyolefin resins, vinyl chloride resins, vinyl acetate resins, fluororesins, (meth)acrylic resins, engineering plastics obtained by vinyl polymerization, and super engineering plastics.

[0083] The polyolefin resin includes homopolymers or copolymers of ethylene, propylene, styrene, butadiene, butylene, isoprene, chloroprene, isobutylene, isoprene, and the like, or a cyclic olefin resin having a norbornene skeleton.

[0084] Vinyl chloride resins include homopolymers or copolymers of vinyl chloride and vinylidene chloride.

[0085] Vinyl acetate resins include polyvinyl acetate which is a homopolymer of vinyl acetate, polyvinyl alcohol which is a hydrolyzate of polyvinyl acetate, polyvinyl acetal which is obtained by reacting formaldehyde, n-butyraldehyde and vinyl acetate, and polyvinyl butyral which is obtained by reacting polyvinyl alcohol, butyraldehyde and the like.

[0086] Fluororesins include homopolymers or copolymers of tetrachloroethylene, hexafluoropropylene, chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride, and perfluoroalkyl vinyl ether.

[0087] (Meth) acrylic resins include homopolymers or copolymers of (meth) acrylic acid, (meth) acrylonitrile, (meth) acrylic acid esters, and (meth) acrylamides, etc. It should be noted that in this specification, "(meth) acrylic acid" means "acrylic acid and / or methacrylic acid".

[0088] (Meth)acrylic acid includes acrylic acid and methacrylic acid.

[0089] (Meth)acrylonitrile: includes acrylonitrile and methacrylonitrile.

[0090] The (meth)acrylate includes alkyl (meth)acrylates, (meth)acrylic monomers having a cycloalkyl group, and alkoxyalkyl (meth)acrylates.

[0091] The alkyl (meth)acrylates include: methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, hydroxyethyl (meth)acrylate, and the like.

[0092] The (meth)acrylic monomer having a cycloalkyl group includes cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and the like.

[0093] The alkoxyalkyl (meth)acrylate includes 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, and the like.

[0094] (Meth)acrylamides include, for example, (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-octyl(meth)acrylamide and other N-substituted(meth)acrylamides.

[0095] (Condensation-polymerized resin)

[0096] The polycondensation resins include amide resins and polycarbonates.

[0097] Amide resins include, for example, aliphatic amide resins such as 6,6-nylon, 6-nylon, 11-nylon, 12-nylon, 4,6-nylon, 6,10-nylon, and 6,12-nylon; aromatic polyamides formed from aromatic diamines such as phenylenediamine; aromatic dicarboxylic acids such as terephthaloyl chloride and isophthaloyl chloride; or derivatives thereof.

[0098] Polycarbonate refers to a reaction product of bisphenol A or its derivatives, namely bisphenols, and phosgene or diphenyl carbonate.

[0099] (Addition Polymerization Resin)

[0100] Addition polymerized resins include ester resins, U polymers, liquid crystal polymers, polyether ketones, polyether ether ketones, unsaturated polyesters, alkyd resins, polyimide resins, polysulfones, polyphenylene sulfide, polyether sulfone, polyurethane resins, and the like.

[0101] Ester resins include aromatic polyesters, aliphatic polyesters, unsaturated polyesters and the like.

[0102] Aromatic polyesters include copolymers of glycols such as ethylene glycol, propylene glycol, and 1,4-butanediol and aromatic dicarboxylic acids such as phthalic acid.

[0103] Aliphatic polyesters include copolymers of glycols and aliphatic dicarboxylic acids such as succinic acid and valeric acid, homopolymers or copolymers of hydroxycarboxylic acids such as glycolic acid and lactic acid, and copolymers of glycols, aliphatic dicarboxylic acids and hydroxycarboxylic acids.

[0104] Unsaturated polyesters include copolymers of glycols, unsaturated dicarboxylic acids such as maleic anhydride, and, if necessary, vinyl monomers such as styrene.

[0105] U polymers include copolymers formed from bisphenol A or its derivatives, namely bisphenols, terephthalic acid, isophthalic acid, and the like.

[0106] Liquid crystal polymers include copolymers of p-hydroxybenzoic acid, terephthalic acid, p,p'-dihydroxydiphenyl ether, p-hydroxy-6-naphthoic acid, polyethylene terephthalate, and the like.

[0107] The polyetherketone includes homopolymers or copolymers such as 4,4'-difluorobenzophenone and 4,4'-dihydrobenzophenone.

[0108] Polyetheretherketone includes copolymers of 4,4'-difluorobenzophenone and hydroquinone.

[0109] Alkyd resins include copolymers formed of higher fatty acids such as stearic acid and palmitic acid, dibasic acids such as phthalic anhydride, and polyols such as glycerol.

[0110] Polyimide resins include: copolymers of polyphthalic anhydride or 4,4'-diaminodiphenyl ether, i.e., pyromellitic acid-type polyimide; copolymers formed from aromatic diamines such as trimellitic anhydride or p-phenylenediamine and diisocyanate compounds, i.e., trimellitic acid-type polyimide; biphenyl-type polyimide formed from biphenyltetracarboxylic acid, 4,4'-diaminodiphenyl ether, and p-phenylenediamine; benzophenone-type polyimide formed from benzophenonetetracarboxylic acid or 4,4'-diaminodiphenyl ether, etc.; bismaleimide-type polyimide formed from bismaleimide or 4,4'-diaminodiphenylmethane, etc.

[0111] Polysulfone includes copolymers of 4,4'-dichlorodiphenyl sulfone or bisphenol A, etc.

[0112] Polyphenylene sulfide includes copolymers of p-dichlorobenzene, sodium sulfide, and the like.

[0113] Polyethersulfones include polymers of 4-chloro-4'-hydroxydiphenylsulfone.

[0114] Polyurethane resins are copolymers of diisocyanates and diols.

[0115] Diisocyanates include: dicyclohexylmethane diisocyanate, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 1,3-cyclohexyl diisocyanate, 1,4-cyclohexyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, etc.

[0116] The diols include: ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, cyclohexanedimethanol and other relatively low molecular weight diols, polyester diols, polyether diols, polycarbonate diols and the like.

[0117] (Addition condensation resin)

[0118] Addition condensation resins include phenolic resins, urea-formaldehyde resins, and melamine resins.

[0119] Phenolic resins include homopolymers or copolymers of phenol, cresol, resorcinol, phenylphenol, bisphenol A, bisphenol F, and the like.

[0120] Urea-formaldehyde resin is a copolymer of formaldehyde and urea.

[0121] Melamine resin is a copolymer of formaldehyde and melamine.

[0122] (Ring-opening polymerization resin)

[0123] Ring-opening polymerization resins include polyalkylene oxides, polyacetals, epoxy resins, and the like.

[0124] The polyalkylene oxide includes homopolymers or copolymers of ethylene oxide, propylene oxide, and the like.

[0125] Polyacetals include copolymers of trioxane, formaldehyde, ethylene oxide, and the like.

[0126] The epoxy resin includes an aliphatic epoxy resin formed from a polyol such as ethylene glycol and epichlorohydrin, an aliphatic epoxy resin formed from bisphenol A and epichlorohydrin, and the like.

[0127] The transparent resin according to one embodiment includes any one of (meth) acrylic resin, polycarbonate resin, cycloolefin resin, polystyrene and acetate resin. In addition, from the viewpoint of improving the clarity of an image, the transparent resin according to one embodiment includes at least one of polyester resin, polysulfone resin, polycarbonate resin and cycloolefin resin.

[0128] (Dispersion Medium)

[0129] The dispersion medium is an organic solvent used in preparing a polymer solution containing a light-transmitting resin composition, and includes, for example, dichloromethane and ethyl acetate. The light-transmitting resin composition according to one embodiment contains 300 to 800 parts by mass of the dispersion medium, preferably 400 to 700 parts by mass of the dispersion medium, and more preferably 500 to 600 parts by mass of the dispersion medium, relative to 100 parts by mass of the transparent resin.

[0130] <Adhesive>

[0131] The adhesive of the present invention comprises a translucent resin composition, which bonds adhered materials of different materials and adhered materials of the same material. In addition, the translucent resin composition is used as an adhesive, for example. The adhesive or adhesive can bond the optical film described later to the substrate. The adhered materials composed of different materials refer to, for example, an organic material and an inorganic material. In addition, the adhered materials of the same material refer to, for example, an organic material and an organic material.

[0132] <Optical Film>

[0133] The optical film includes: a layer composed of a translucent resin composition, and a film-like layer formed by heat-melting the translucent resin composition. The optical film to which the present invention relates includes not only a single optical film, but also a method in which an optical film is provided on at least one side of a substrate. It should be noted that the state of the layer composed of the translucent resin composition is liquid before curing and drying, and solid after curing and drying. In other words, after the translucent resin composition is cured and dried, the optical film has no adhesiveness. At this time, the optical film can be bonded to the substrate by the above-mentioned adhesive and / or bonding agent.

[0134] The thickness of the optical film (excluding the substrate) according to one embodiment is 1 μm to 120 μm, preferably 5 μm to 110 μm, and more preferably 10 μm to 100 μm.

[0135] The substrate is, for example, a glass substrate, a plastic substrate, and a plastic film (PET film, etc.) treated with silane.

[0136] The method of applying the light-transmitting resin composition to the substrate includes, for example, rod coating, knife coating, roll coating, blade coating, die coating, gravure coating, etc. After the light-transmitting resin composition is applied to the substrate by any of the above methods to form a coating film, it is cured and dried at 60°C to 200°C, preferably 70°C to 170°C, and more preferably 80°C to 140°C.

[0137] From the viewpoint of obtaining a depolarization effect, the polarization degree (%) of the optical film according to one embodiment is preferably 90% or less, and more preferably 87% or less.

[0138] From the viewpoint of suppressing the change in the image color of the display screen, the haze (%) of the optical film according to one embodiment is preferably 50 or less, and more preferably 40 or less.

[0139] From the viewpoint of suppressing the change in the image color of the display screen, the chromaticity change amount of the optical film according to one embodiment is preferably 0.04 or less, and more preferably 0.02 or less.

[0140] From the viewpoint of suppressing the change in the image color of the display screen, the contrast ratio of the optical film according to one embodiment is preferably 70% or more, and more preferably 75% or more.

[0141] <Display device>

[0142] Figure 3 It is an exploded perspective view showing an example of the display device according to the present embodiment. The optical film 1 and the adhesive (not shown) described below include the light-transmitting resin composition according to the present invention, and therefore detailed description of the light-transmitting resin composition is omitted.

[0143] A display device that emits light in a polarized state according to one embodiment includes at least one of an optical film and a pressure-sensitive adhesive disposed on the viewer side of the display device. At least one of the optical film and the pressure-sensitive adhesive according to one embodiment contains a light-transmitting resin composition.

[0144] The display device 100 is a device that emits light in a polarized state, and includes, for example, a liquid crystal display device (hereinafter also referred to as LCD) and an organic EL display. The display device 100 has a structure in which a backlight 101, a polarizing plate 102, a phase difference film 103, a glass substrate 104 with a transparent electrode, a liquid crystal layer 105, a glass substrate 106 with a transparent electrode, an RGB color filter 107, a phase difference film 108, a polarizing plate 109, and the optical film 1 of this embodiment are stacked in this order. In addition, from the perspective of protecting the screen of the display device 100, a protective film (for example, a PET film) not shown in the figure may also be provided between the polarizing plate 109 and the optical film 1. Moreover, the optical film 1 may be bonded to the polarizing plate 109 or the protective film (not shown) by the adhesive of the present invention or a known adhesive. Here, the display device 100 may have a structure in which the optical film 1 of the present invention and the adhesive are assembled into a liquid crystal display device of a known structure. In addition, the display device 100 may not have the optical film 1 as an essential structure, and may only have the adhesive of the present invention. The adhesive of the present invention has the same depolarization effect as the optical film 1. Figure 3 As shown, the optical film 1 may be provided on the polarizing plate 109. For example, one or more optical films 1 may be arranged at any position between the backlight 101 and the polarizing plate 109.

[0145] In the display device 100, the optical film 1 is assembled on the side closer to the observer than the polarizing plate 109, that is, on the side opposite to the backlight 101. Therefore, the light emitted from the polarizing plate 109 is incident on the optical film 1 and emitted in a randomized manner with its polarization state. As a result, when the user (observer) observes through polarized sunglasses, black vision will not occur in the display screen of the display device 100, and the color change of the image can be suppressed. In addition, when the user observes the display screen from an oblique direction without wearing polarized sunglasses, the color of the image on the display screen sometimes changes in the same way. This is because the light from the oblique direction is partially polarized, so it produces the same effect as if a weak polarizing plate is placed, that is, the same effect as wearing polarized sunglasses.

[0146] In addition, recently, display device 100 is designed in such a way that by changing the type of liquid crystal and using a viewing angle compensation film, the brightness and color of the image when the user views the display device 100 obliquely do not change. Generally speaking, most users use a display device 100 with a protective film having various functions attached thereto in order to prevent scratches, light reflection, and blue light on the screen of the display device 100 (such as a smartphone, a tablet terminal, various displays, etc.). However, since the protective film (for example, a polyester film) has birefringence, the following problem occurs: when the user views the screen of the display device 100 obliquely, the color of the image changes (specifically, rainbow mottling on the screen). Therefore, the present invention (at least one of the optical film and the adhesive) has the following effect: even when the user does not wear polarized sunglasses to visually identify a television or a sign, or when a protective film adheres to the screen of the display device 100, the color change of the same image is suppressed. In addition, the present invention can suppress costs as compared with the conventional methods (for example, a zero-birefringence film and a super-birefringence film) for suppressing the color change of an image caused by a protective film.

[0147] <Manufacture of a Transparent Resin Composition>

[0148] Table 1 shows the transparent resins and the refractive indices of the transparent resins used when manufacturing the transparent resin compositions of Production Examples 1 to 9. The acrylic adhesive of Production Example 9 means a polymer obtained by copolymerizing 20 parts by mass of BA and 80 parts by mass of PHEA with respect to 100 parts by mass of the transparent resin.

[0149] [Table 1]

[0150]

[0151] ※Explanation of Abbreviations

[0152] PMMA: Acrylic Resin

[0153] PC: Polycarbonate

[0154] BA: Butyl Acrylate

[0155] PHEA: Phenoxyethyl Acrylate

[0156] Table 2 shows the natural fibers and the average particle diameters (unit: μm) of the natural fibers used when manufacturing the transparent resin compositions of Production Examples 1 to 9.

[0157] [Table 2]

[0158]

[0159] Table 3 shows the raw material blending of the transparent resin, natural fiber, and solvent used when producing the light-transmitting resin compositions of Examples 1 to 9.

[0160] [Table 3]

[0161]

[0162] ※The values ​​in the table indicate the mass parts of the active ingredients.

[0163] Explanation of abbreviations

[0164] PMMA: acrylic resin

[0165] PC: Polycarbonate

[0166] BA: Butyl acrylate

[0167] PHEA: Phenoxyethyl acrylate

[0168] (Example 1)

[0169] Based on the raw material blending of Example 1 in Table 3, 2 g of silk powder SP (Izumi Senko Co., Ltd.) as a natural fiber (active ingredient: 2 parts by mass) and an appropriate amount of dichloromethane (Wako Pure Chemical Industries, Ltd.) as a solvent (5 to 6 times the mass of PMMA) were added to a vial. After the natural fiber was fully dispersed in the solvent using an ultrasonic cleaner, 100 g of PMMA (Wako Pure Chemical Industries, Ltd.) particles (active ingredient: 100 parts by mass) as a transparent resin were added to the vial. The mixture in the vial was stirred with an oscillator until the transparent resin was completely dissolved to prepare a polymer solution.

[0170] The polymer solution is spread in the form of a sheet on a peeling PET film and cast by a coater. The cast film spread on the PET film is dried at room temperature (20-25°C) for one hour. The dried cast film is peeled off from the PET film, and the cast film is sandwiched between paper and glass and dried at 90°C for more than 10 hours under a reduced pressure environment. Thus, an optical film with a thickness of 50 μm is obtained. It should be noted that the thickness of the optical film is measured using a dial thickness gauge (Peacock: Ozaki Manufacturing Co., Ltd.).

[0171] (Examples 2 to 8)

[0172] Examples 2 to 8 were performed in the same manner as in Example 1 based on the raw material blending amounts in Table 3 to obtain light-transmitting resin compositions and optical films.

[0173] (Example 9)

[0174] Example 9 Based on the raw material compounding amounts in Table 3, the same process as in Example 1 was performed to obtain an adhesive of a light-transmitting resin composition. It should be noted that in Example 9, the adhesive of the light-transmitting resin composition was applied to a glass substrate and dried to prepare an "optical test piece". It should be noted that the "optical test piece" of Example 9 was prepared to confirm whether useful optical properties can be obtained not only as an optical film but also as an adhesive.

[0175] (Comparative Examples 1 to 10)

[0176] Table 4 shows the transparent resin used in the manufacture of the translucent resin composition of Comparative Examples 1 to 4 and 6 and the refractive index of the transparent resin. It should be noted that the 1 / 4 phase difference plates of Comparative Examples 5, 8, and 9 and the PET film of Comparative Example 7 have nothing to do with the manufacture of the translucent resin composition. That is, Comparative Examples 5 and Comparative Examples 7 to 9 are used to compare the performance with the optical films of Examples 1 to 8 and the optical test piece of Example 9. Here, Comparative Example 7 (PET film) is used to compare with Examples 3, 5, and 6 for the rainbow mottle evaluation described later. In addition, the optical properties of the 1 / 4 phase difference plates of Comparative Examples 5, 8, and 9 are described. Comparative Example 5 (QWP-1) is a 1 / 4 phase difference plate of normal dispersion, which has the characteristic that the delay amount decreases as the wavelength becomes high in the visible light region. On the other hand, Comparative Examples 8 and 9 (QWP-2, QWP-3) are 1 / 4 phase difference plates of reverse dispersion, which have the characteristic that the delay amount increases as the wavelength becomes high in the visible light region. However, the 1 / 4 phase difference plates of Comparative Examples 8 and 9 have the problem that it is difficult to accurately control the phase difference of 1 / 4 wavelength in the entire visible light region. Therefore, Comparative Examples 5, 8, and 9 are used for comparison with Examples 3, 5, and 6, which can eliminate the problems related to the control of the 1 / 4 wavelength phase difference in the entire visible light region.

[0177] [Table 4]

[0178]

[0179] ※Explanation of abbreviations

[0180] PSU: Polysulfone resin

[0181] PC: Polycarbonate

[0182] PET: Polyethylene terephthalate

[0183] QWP-1: 1 / 4 phase difference plate with normal dispersion (MCR140N, MeCan Imaging Inc.)

[0184] QWP-2: Reverse dispersion 1 / 4 phase difference plate (#14-724, Edmund Optics Inc.)

[0185] QWP-3: Reverse dispersion 1 / 4 phase difference plate (#88-252, Edmund Optics Inc.)

[0186] Table 5 shows the non-natural fibers and the average particle size (in μm) of the non-natural fibers used in the manufacture of the translucent resin compositions of Comparative Examples 1 to 4, 6, and 10. It should be noted that, as mentioned above, Comparative Examples 5, 7 to 9 are not related to the manufacture of the translucent resin composition, so no natural fibers are used. In order to confirm the optical properties of the translucent resin composition of Comparative Example 6 when no natural fibers and non-natural fibers are contained, no natural fibers and non-natural fibers are used. In Comparative Example 10, 8 translucent resin compositions were manufactured using calcite with an average particle size ranging from 0.9 μm to 22.5 μm as non-natural fibers. It should be noted that the range of the average particle size of 0.9 μm to 22.5 μm includes 0.9 μm, 2.1 μm, 2.6 μm, 3.6 μm, 7.3 μm, 14.3 μm, 19.2 μm, and 22.5 μm.

[0187] [Table 5]

[0188]

[0189] ※Explanation of abbreviations

[0190] Calcite: Made by crushing calcium carbonate crystals (calcite).

[0191] PET: Made by crushing polyester film at ultra-low temperatures.

[0192] Table 6 shows the raw material blending of the transparent resin, non-natural fiber and solvent used in the manufacture of the translucent resin compositions of Comparative Examples 1 to 4, 6 and 10. In Comparative Example 10, as described above, 8 types of translucent resin compositions were manufactured using calcite having average particle sizes ranging from 0.9 μm to 22.5 μm. It should be noted that in Comparative Examples 5, 7 to 9, the manufacture of the translucent resin composition was not carried out, and the finished products (PET films, QWP-1 to QWP-3 as 1 / 4 phase difference plates) described in Table 6 were prepared.

[0193] [Table 6]

[0194]

[0195] ※The values ​​in the table indicate the mass parts of the active ingredients.

[0196] <Test method>

[0197] The following Test Examples 1 to 9 were conducted using a display device equipped with optical films (Examples 1 to 8, Comparison Examples 1 to 4, 6, and 10), an optical test piece (Example 9), a PET film (Comparison Example 7), and a 1 / 4 phase difference plate (Comparison Examples 5, 8, and 9), and performance evaluation related to optical properties was performed.

[0198] (Test Example 1: Confirmation of polarization elimination)

[0199] An optical film, an optical test piece, or a quarter phase difference plate is attached to the display screen of a display device (tablet terminal, Apple), and the optical film, optical test piece, or quarter phase difference plate is covered with a polarizing plate in a manner to form an orthogonal Nicol state, and a white image is displayed on a liquid crystal display device. At this time, the liquid crystal display device is visually observed, and the effect of eliminating polarization is evaluated based on the following evaluation criteria.

[0200] (Evaluation Criteria)

[0201] Yes: This is a brightness level at which the image on the display screen can be visually recognized.

[0202] None: The brightness is not such that the image on the display screen can be visually recognized.

[0203] (Test Example 2: Measurement of Polarization Degree)

[0204] A white image is displayed on a liquid crystal display device to which an optical film, an optical test piece or a 1 / 4 phase difference plate is adhered, in a parallel Nicol state or an orthogonal Nicol state. When the brightness measured in the parallel Nicol state is set to Lp and the brightness measured in the orthogonal Nicol state is set to Lc, the degree of polarization is calculated by the following formula 2. The degree of polarization is an indicator of the degree to which light is close to complete polarization. For example, when the value of the degree of polarization is 100%, it indicates light in a completely single polarization state. On the other hand, when the value of the degree of polarization is 0%, it indicates complete lack of polarization (or, non-polarization). In the case where polarization components are mixed, the degree of polarization takes a value between 0 and 100% according to the ratio of the polarization components. It should be noted that a spectroradiometer (CS-2000A, Konica Minolta, Ltd.) is used to measure the brightness.

[0205]

[0206] (Test Example 3 Measurement of Haze Value)

[0207] The haze value (turbidity value) of the optical film, optical test piece and 1 / 4 phase difference plate was measured using a haze meter (SH7000, Nippon Denshoku Industries Co., Ltd.). The haze value indicates the degree of turbidity of the measured object. It should be noted that the smaller the haze value, the more transparent the measured object.

[0208] (Test Example 4 Measurement of Chromaticity Change)

[0209] The chromaticity (u') of the liquid crystal display device attached with an optical film, an optical test piece or a 1 / 4 phase difference plate in the parallel Nicol state was measured using a spectroradiometer (CS-2000A, Konica Minolta Co., Ltd.). p , v' p ) and the chromaticity (u') in the orthogonal Nicol state c , v' c ). The measured chromaticity is a value based on the CIE 1976UCS chromaticity diagram. It should be noted that when measuring the chromaticity, the 24 colors of the Macbeth color chart are displayed on the liquid crystal display device respectively, and the chromaticity change Δu'v' relative to the 24 colors is measured. The largest chromaticity change Δu'v' among the chromaticity changes Δu'v' relative to each of the 24 colors is used as the measured value. Here, the chromaticity change Δu'v' is calculated based on the chromaticity measured in the parallel Nicol state and the orthogonal Nicol state and Formula 3. The smaller the value of the chromaticity change Δu'v', the less likely the user is to feel the color change of the image.

[0210]

[0211] (Test Example 5: Confirmation of Visibility)

[0212] Characters were displayed on a display screen of a liquid crystal display device to which an optical film, an optical test piece or a quarter phase difference plate was attached. The characters on the display screen were visually observed under crossed Nicols, and the clarity was evaluated based on the following four-level evaluation criteria.

[0213] (Evaluation Criteria)

[0214] ◎: The text display is very clear.

[0215] ○: The text is displayed clearly.

[0216] △: The text is slightly clearer.

[0217] ×: The text is displayed blurry.

[0218] (Test Example 6: Contrast Measurement)

[0219] The maximum brightness L when a white image is displayed on the display screen of a liquid crystal display device (hereinafter referred to as the measurement method) to which an optical film, an optical test piece or a 1 / 4 phase difference plate is attached is measured using a spectroradiometer (CS-2000A, Konica Minolta Co., Ltd.). max and the minimum brightness L when displaying a black imagemin Based on the maximum brightness L max , minimum brightness L min The contrast ratio is calculated using Formula 4. A higher contrast ratio indicates a brighter display in which the difference in color is more clearly expressed.

[0220] Contrast ratio = L max / L min (Formula 4)

[0221] It should be noted that the contrast ratio when a white image is displayed on the display screen of a liquid crystal display device in a manner without adhering an optical film, an optical test piece or a 1 / 4 phase difference plate (hereinafter referred to as the normal mode) is 1119. Here, in order to evaluate the change in contrast during the measurement mode, the ratio of the contrast ratio is calculated based on the following formula 5. As mentioned above, the contrast ratio during the normal mode is "1119". This means that the closer the value of the contrast ratio ratio is to 100%, the less the contrast ratio decreases during the measurement mode.

[0222] Contrast ratio ratio = (contrast ratio in measurement mode / contrast ratio in normal mode) × 100 (%) (Formula 5)

[0223] (Test Example 7 Evaluation of Rainbow Mottle)

[0224] Figure 5 A schematic diagram for illustrating the method of evaluating rainbow mottle is shown. Using a spectroradiometer (CS-2000A, Konica Minolta, Inc.), the chromaticity (u', v') of an LCD (MediaPad M3 lite, Huawei Device Co., Ltd.) adhered with the optical films of Examples 3, 5, and 6 (hereinafter referred to as Measurement Method 1), an LCD in which a PET film is also arranged between the optical film and the LCD in Measurement Method 1 (hereinafter referred to as Measurement Method 2), and an LCD adhered with the PET film of Comparative Example 7 (hereinafter referred to as Measurement Method 3) were measured. The purpose of the test of Measurement Method 2 is to confirm the effect of eliminating rainbow mottle when the optical films of Examples 3, 5, and 6 are attached relative to the PET film on the LCD. The PET film is adhered in a manner such that the slow axis is parallel to the light transmission axis of the polarizing plate on the visual recognition side of the LCD (since the optical film has no slow axis, it is adhered in an arbitrary direction). Here, in order to reduce the refractive index difference at the film interface, an appropriate amount of water is inserted between each film (optical film or PET film) and the LCD and between the films (optical film and PET film) to adhere them. The angle of the LCD is expressed by the elevation angle θ and the azimuth angle θ is defined as the angle between 0° when the display is facing forward and 90° when facing sideways. is the angle of the light transmission axis on the visual recognition side of the LCD relative to the rotation axis of θ (refer to Figure 5 ).right Figure 5 In the fixed The chromaticity (u', v') at each viewing angle when θ is rotated from 0° to 80° (hereinafter referred to as measurement condition 1) and the chromaticity (u', v') at each viewing angle when θ is fixed at 65° The chromaticity (u', v') at each viewing angle when rotating from 0° to 90° (hereinafter referred to as measurement condition 2) was measured. The rainbow unevenness of the LCD display screen was evaluated based on the following evaluation criteria.

[0225] (Evaluation Criteria)

[0226] ○: The difference between the maximum value and the minimum value of u' and v' in both measurement condition 1 and measurement condition 2 is less than 0.02.

[0227] ×: The difference between the maximum value and the minimum value of u' or v' in both measurement condition 1 and measurement condition 2 is 0.02 or more.

[0228] (Test Example 8 Evaluation of Transmittance Wavelength Dependency)

[0229] Figure 6 This is a schematic diagram for explaining the evaluation method of the wavelength dependence of transmittance. Polarizing plates are installed on the light source side and the detector side of the haze meter (SH7000, Nippon Denshoku Industries Co., Ltd.), and the optical films of Examples 3, 5, and 6 or QWP-1 to QWP-3 of Comparative Examples 5, 8, and 9 are placed between the two polarizing plates. The transmittance at a wavelength of 400nm to 750nm is measured. Here, the transmittance measured in the parallel Nicol state without the optical film and QWP-1 to QWP-3 is set to 100%. The polarizing plate on the detector side ( Figure 6 The analyzer (Analyzer) is rotated to switch between the parallel Nicol state and the orthogonal Nicol state. The transmittance spectrum measured at a wavelength of 400nm to 750nm is normalized by the transmittance at 550nm, and the transmittance wavelength dependence of Examples 3, 5, 6 and Comparative Examples 5, 8, and 9 is evaluated based on the following evaluation criteria.

[0230] (Evaluation Criteria)

[0231] ○: The normalized transmittance is 90% to 110% at a wavelength of 400 nm to 750 nm in the parallel Nicol state and the orthogonal Nicol state.

[0232] ×: The normalized transmittance is outside the range of 90% to 110% at a wavelength of 400 nm to 750 nm in the parallel Nicol state and the orthogonal Nicol state.

[0233] (Test Example 9: Evaluation of clarity due to difference in pixel pitch)

[0234] The purpose of Test Example 9 is to confirm the image clarity when an optical film is adhered to two displays with different pixel pitches. In the state without a polarizing plate and in the orthogonal Nicol state (using a polarizing plate), the optical films of Examples 3, 5, 6, Comparative Example 2 or Comparative Example 10 (8 kinds) are adhered to displays with two pixel pitches (pixel pitch of 96μm×96μm, pixel pitch of 294μm×294μm) (using matching oil with a refractive index of 1.518). The clarity of the display formed by adhering each optical film was visually measured. The display with a pixel pitch of 96μm×96μm (called a small pixel pitch) is iPad (registered trademark, 4th generation, Apple). The display with a pixel pitch of 294μm×294μm (called a large pixel pitch) is CD-AD198GEB-X (I-ODATA Co., Ltd.). Here, pixel pitch refers to the distance between adjacent pixels. The smaller the pixel pitch, the higher the resolution per unit area. The clarity was evaluated based on the following evaluation criteria.

[0235] (Evaluation Criteria)

[0236] ◎: The text display is very clear.

[0237] ○: The text is displayed clearly.

[0238] △: The text is slightly clearer.

[0239] ×: The text is displayed blurry.

[0240] <Test Results>

[0241] Table 7 shows the test results of Examples 1 to 9. Table 8 shows the test results of Comparative Examples 1 to 10. The "-" in Table 7 indicates that the test was not carried out. It should be noted that in Comparative Example 6 in Table 8, since the polarization elimination was "none", the test items (polarization degree, chromaticity change, contrast) were not measured (illustrated by "-" in Table 8). The "-" in Table 8 indicates that the test was not carried out.

[0242] Figure 7A to Figure 7H The measurement condition 1 is shown ( Chromaticity measurement results of Reference Example, Examples 3, 5, 6, and Comparative Example 7 (θ = 0 to 80°). Figure 8A to Figure 8H The measurement condition 2 (θ = 65°, ) and the chromaticity measurement results of the reference example, embodiments 3, 5, 6, and comparative example 7. Here, the reference example represents an LCD formed without adhering an optical film and a PET film. In embodiments 3, 5, and 6, the chromaticity (u', v') was measured in measurement method 1 and measurement method 2. Measurement method 1 represents a method in which only RDF (referring to the optical film) is adhered to the LCD. Measurement method 2 represents a method in which both PET and RDF (referring to the optical film) are adhered to the LCD.

[0243] use Figure 7A to Figure 7H as well as Figure 8A to Figure 8H The following is a qualitative evaluation of the rainbow mottle of LCD. Fig. 7A No rainbow spots are generated in the LCD of the reference example. Figure 7B to Figure 7G The existence range of the chromaticity (u', v') locus relative to the v' axis and the u' axis is roughly the same as Fig. 7A The chromaticity locus has the same range, so Figure 7B to Figure 7G The LCD does not produce rainbow mottle. On the other hand, Figure 7H The existence range of the chromaticity (u', v') trajectory is greater than Fig. 7A The existence range of the chromaticity locus, therefore Figure 7H Rainbow spots are produced in the LCD.

[0244] Likewise, pre-determining Fig. 8A No rainbow spots are generated in the LCD of the reference example. Figure 8B to Figure 8G The existence range of the chromaticity (u', v') locus relative to the v' axis and the u' axis is roughly the same as Fig. 8A The chromaticity locus has the same range, so Figure 8B to Figure 8G The LCD does not produce rainbow mottle. On the other hand, Figure 8H The existence range of the chromaticity (u', v') trajectory is greater than Fig. 8A The existence range of the chromaticity locus, therefore Figure 8H The rainbow mottle is generated in the LCD. Tables 7 and 8 show the Figure 7B to Figure 7H , Figure 8B to Figure 8H And the detailed evaluation results of the evaluation criteria of Test Example 7. As shown in Table 7, Examples 3, 5, and 6 have a significant effect of suppressing rainbow spots on LCDs in both Measurement Method 1 and Measurement Method 2.

[0245] Fig.9A This is a graph showing the wavelength dependence of transmittance of Example 3 and Comparative Examples 5, 8, and 9 in a parallel Nicol state. Fig. 9B Graph showing the wavelength dependence of transmittance of Example 3 and Comparative Examples 5, 8, and 9 under the orthogonal Nicol state. FIG. 9A to FIG. 9BIn Example 3, the normalized transmittance takes a value in the range of 90% to 110% in the wavelength range of 400nm to 750nm. That is, in Example 3, there is no wavelength dependence of the transmittance, and the color change of the image can be suppressed in the visible light region. On the other hand, in Comparative Examples 5, 8, and 9, the normalized transmittance takes a value outside the range of 90% to 110% at a part of the wavelengths of 400 to 750nm. That is, in Comparative Examples 5, 8, and 9, there is wavelength dependence of the transmittance, so the color of the image changes at a specific wavelength in the visible light region where the normalized transmittance exceeds or falls below the specified value (90% to 110%).

[0246] [Table 7]

[0247]

[0248] ※Remark

[0249] The test item without PET film is equivalent to measurement method 1.

[0250] The test items include PET film equivalent to measurement method 2.

[0251] [Table 8]

[0252]

[0253] The followings are known from the results of Tables 7 and 8. In particular, the optical properties (polarization degree, haze, chromaticity change, sharpness, contrast) of Example 3 are improved compared to the optical properties of Comparative Examples 1 to 2 and 10 (the case of containing calcite (calcium carbonate) as an inorganic material). The optical properties (rainbow mottle evaluation, transmittance wavelength dependence, sharpness due to the difference in pixel pitch) of Examples 3, 5, and 6 are superior to those of Comparative Examples 2 and 7 to 10.

[0254] Here, the sharpness caused by the difference in pixel pitch of Examples 3, 5, and 6 is supplemented. The evaluation results of the sharpness caused by the difference in pixel pitch of Examples 3, 5, and 6 show such a significant effect that the sharpness of the image of the display with a large pixel pitch is improved. Recently, large displays are used in all places such as stations, restaurants, supermarkets, shopping malls, pharmacies, hospitals, hotels, banks, schools, offices, etc. as digital signage (electronic billboards). However, in the prior art, the sharpness of the image displayed in the large display set up in various places is insufficient, so sometimes users find it difficult to visually recognize the content of the image. The optical film of the present invention is bonded to the large display, so that the image on the display screen becomes sharp, thereby improving the visual recognition of the image by the user. In addition, even if the resolution of the large display is increased to 4K or 8K through future technological innovations, it is expected that the pixel pitch will not be less than 100μm×100μm. In this way, since the present invention can improve the sharpness of the image displayed on the large display, it can realize rich image performances in various places in the future compared with the past.

[0255] Figure 4 A is a diagram showing an image obtained by photographing a display screen to which the optical film of Example 3 is attached in a crossed Nicol state. Figure 4 B is a diagram showing an image obtained by photographing a display screen to which the optical film of Comparative Example 1 is attached in a crossed Nicol state. Figure 4 In A, for example, "Keio University" is clearly displayed, and the parts 400 (blue), 410 (yellow), and 420 (red) constituting the Keio University seal are displayed in the colors they should be displayed. Figure 4 In B, "Keio University" is not clearly displayed, and the colors of the parts 500, 510, and 520 that make up the Keio University seal are different from those in the Figure 4 A is displayed in a color that reduces its visibility. For example, Figure 4 The portion 400 of A is shown in blue, while Figure 4 The portion 500 of B is displayed in black. Thus, in the optical films containing calcite (Comparative Examples 1 and 2), there is a problem that the color of the image on the display screen changes to a color different from the color that should be displayed.

[0256] The optical properties (polarization degree, haze, sharpness, contrast) of Example 3 are improved compared with the optical properties of Comparative Examples 3 and 4 (the case where PET is contained as the synthetic polymer material).

[0257] The optical characteristics (chromaticity change) of Example 3 are improved compared to those of Comparative Examples 5, 8, and 9 (when using a quarter phase plate). In particular, Example 3 can suppress color changes of the image on the display screen when the user visually recognizes the display device.

[0258] The optical properties (polarization elimination) of Example 1 are improved compared to the optical properties of Comparative Example 6 (the case containing no natural fibers, etc.). This shows that the polarization state cannot be eliminated when the light-transmitting resin composition contains neither natural fibers nor non-natural fibers.

[0259] As described above, the present invention has a remarkable effect of suppressing a change in the color of an image on a display screen when a user observes the display screen.

[0260] The present invention is not limited to the above-described embodiments, and various modifications and changes can be made within the scope of the gist of the invention.

[0261] This application claims priority based on Japanese patent application No. 2022-120674 filed on July 28, 2022, the entire contents of which are incorporated herein by reference.

Claims

1. A light-transmitting resin composition comprising: Transparent resin; and Natural fibers with an average particle size of 2μm to 100μm, The light-transmitting resin composition is used to eliminate polarization.

2. A light-transmitting resin composition comprising: Transparent resin; and Natural fibers having a maximum retardation of 300 nm to 1300 nm and an average particle size of 2 μm to 100 μm, The light-transmitting resin composition contains 1 to 20 parts by mass of the natural fiber relative to 100 parts by mass of the transparent resin. The light-transmitting resin composition is used to eliminate polarization.

3. The light-transmitting resin composition according to claim 1, wherein The birefringence Δn of the natural fiber is 0.013 to 0.15, The light-transmitting resin composition contains 1 to 20 parts by mass of the natural fiber relative to 100 parts by mass of the transparent resin.

4. The light-transmitting resin composition according to claim 1 or 2, wherein The natural fibers include at least one of plant fibers and animal fibers.

5. The light-transmitting resin composition according to claim 1 or 2, wherein The natural fibers include any of cellulose fibers, cotton, silk and wool.

6. The light-transmitting resin composition according to claim 1 or 2, wherein The transparent resin includes any of vinyl resins, condensation polymerization resins, addition polymerization resins, addition condensation resins, and ring-opening polymerization resins.

7. The light-transmitting resin composition according to claim 6, wherein The transparent resin includes any of a polyolefin resin, a vinyl chloride resin, a vinyl acetate resin, a fluororesin, and a (meth)acrylic resin.

8. The light-transmitting resin composition according to claim 6, wherein The transparent resin includes any of a polyester resin, a polysulfone resin, a polycarbonate resin, and a cycloolefin resin.

9. The light-transmitting resin composition according to claim 6, wherein The transparent resin includes a homopolymer or a copolymer of (meth)acrylate.

10. An adhesive for bonding materials to be bonded. The adhesive comprises the light-transmitting resin composition according to claim 1 or 2. 11 . An optical film comprising the light-transmitting resin composition according to claim 1 or 2.

12. A display device that emits light of a polarization state, The display device includes at least one of an optical film and an adhesive disposed on the viewer side of the display device. At least one of the optical film and the adhesive comprises the light-transmitting resin composition according to claim 1 or 2 .

Citation Information

Patent Citations

  • Liquid crystal display device

    JP2005352068A

  • Depolarization material, depolarization element using the same, and liquid crystal display

    JP2008310310A

  • Depolarizing film, manufacturing method for it and liquid crystal display device

    JP2009217192A

  • Visibility improving method of liquid crystal display device, and liquid crystal display device using the same

    JP2011107198A

  • Drain trap

    JP2022120674A